2020
DOI: 10.1080/10803548.2020.1834232
|View full text |Cite
|
Sign up to set email alerts
|

Standing and sitting postures at work and symptoms of venous insufficiency – results from questionnaires and a Doppler ultrasound study

Abstract: Chronic venous insufficiency is the most common vascular disease. One of the major risk factors for its development is long-term sitting or standing in the same position and the nature of the work performed. This study aimed to evaluate the incidence of chronic venous insufficiency in a group of persons employed in workplaces with a predominance of standing or sitting positions, and to determine work-related and non-work risk factors. The research used two tools: questionnaires and medical examinations. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Approximately between 1960 and 1990, all literature reported regarding signs and symptoms is not available online, only historical record; nonetheless, titles focus almost solely on signs provoked by venous stasis, along with different surgical approaches [8][9][10][11][12][13][14][15][16][17] . In most recent studies, few of them exclusively concentrate on symptoms, and as shown in table 2 1,[18][19][20][21] , none of them report pattern presentation [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…Approximately between 1960 and 1990, all literature reported regarding signs and symptoms is not available online, only historical record; nonetheless, titles focus almost solely on signs provoked by venous stasis, along with different surgical approaches [8][9][10][11][12][13][14][15][16][17] . In most recent studies, few of them exclusively concentrate on symptoms, and as shown in table 2 1,[18][19][20][21] , none of them report pattern presentation [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…However, possible disadvantages in maintaining a prolonged standing posture can occur. Epidemiological studies suggested that prolonged standing might be related to health problems such as venous insufficiency ( 59 ), decreased cognition or discomfort ( 60 ), and back pain ( 61 ). Occupational standing has been associated with elevated low back pain.…”
Section: Strategies To Increase Neat At Workmentioning
confidence: 99%
“…Many workers are required to stand for long periods of time, these workers include nurses, teachers, shop assistants, cooks, pharmacists, and hairdressers, or sit, such as office workers, drivers, and information technology specialists [ 1 , 2 ]. In Dutch standing work guidelines, more than 1 h of continuous standing and more than 4 h of standing in total is unsafe and places the individual at a high risk of strain and health problems, and for which immediate intervention to reduce the strain should be performed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%